On-Farm Application of Biofertilizer and Chemical Fertilizers on Lentil in Three Farmers’ Field of Bangladesh - Bhuiyan, Md Abdul Haque; Md Kamruzzaman, Mollah; Islam, Md Sirajul; Ahmad, Kawsar Uddin (Bangladesh Journal of Microbiology, 2018)
Abstract not available Bangladesh J Microbiol, Volume 33, Number 1-2, June-Dec 2016, pp 35-38